Ability to Write Anecdote Text by Using Caricature Media on 10th Grade Students of SMA Swasta Swakarya Binjai - M. Natsir; Bahagia Saragih; Rafika Dewi (Randwick International of Education and Linguistics Science Journal, 2021)
This study aims to determine the effect of caricature media on the ability to write anecdote text on 10th Grade Students of SMA Swasta Swakarya Binjai School Year 2018/2019. The population of this research is 125 students. Of the 125 students, a sample of 35 students are selected who were taken using a random sample. The method used in this study is a quasih experimental two group post-test design. The instrument used to collect data is the description test. Hypothesis testing is done using the "t" test. The data obtained show that the students 'ability to write anecdote text without using caricature media is in the sufficient category with the mean value obtained by the students is 66.04, while the students' ability to write anecdote texts using caricature media is classified as good with average. (mean) obtained by students 76.6. Furthermore, the hypothesis test shows t_o> t_ (table) and 7.23> 2.03 at the significant level α = 0.05. Thus, it means that H0 is rejected and Ha is accepted, which means that there is an influence of caricature media on the ability to write anecdote text on 10th Grade Students of SMA Swasta Swakarya Binjai School Year 2018/2019. Based on the data analysis above, it can be concluded that the results of learning to write anecdote text using caricature media have a positive effect on students' ability to write anecdote text.